2005
DOI: 10.1103/physrevlett.94.146104
|View full text |Cite
|
Sign up to set email alerts
|

Bond Breaking Coupled with Translation in Rolling of Covalently Bound Molecules

Abstract: The response of a C60 molecule to manipulation across a surface displays a long range periodicity which corresponds to a rolling motion. A period of three or four lattice constants is observed and is accompanied by complex subharmonic structure due to molecular hops through a regular, repeating sequence of adsorption states. Combining experimental data and ab initio calculations, we show that this response corresponds to a rolling motion in which two of the four Si-C60 covalent bonds act as a pivot over which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 25 publications
4
93
1
1
Order By: Relevance
“…2,44,68 For the investigations of individual molecules, lateral manipulation can be used to place molecules at different adsorption sites 6,69,70 or molecular motion itself can be studied. 44,[71][72][73] On the other hand, adsorbates can be picked up and dropped with the probe tip, which is referred to as vertical manipulation. 74,75 Vertical manipulation can also be employed for studying the contact of individual molecules with the STM tip.…”
Section: 65mentioning
confidence: 99%
“…2,44,68 For the investigations of individual molecules, lateral manipulation can be used to place molecules at different adsorption sites 6,69,70 or molecular motion itself can be studied. 44,[71][72][73] On the other hand, adsorbates can be picked up and dropped with the probe tip, which is referred to as vertical manipulation. 74,75 Vertical manipulation can also be employed for studying the contact of individual molecules with the STM tip.…”
Section: 65mentioning
confidence: 99%
“…The behaviour of the fullerene cages upon silicon is therefore intrinsically very important to the feasibility of such systems and has been studied both computationally [1][2][3][4] and experimentally [5][6][7][8][9][10][11]. Experimental studies have also examined the manipulation of the cage upon the surface by a suitable device, most often a scanning tunnelling microscope (STM) tip [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to move the molecules both parallel and perpendicular to the dimer rows upon the surface at room temperature although the success rate parallel to the rows is much higher [13]. A combination of experimental work and abinitio studies have explored the details behind the movement of the C 60 across the surface [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [6][7][8][9][10][11][12] have been carried out experimentally which show that the C 60 molecule adsorbs in the dimer trench at room temperature, and is only observed above the dimer row when the system is heated. A study of the larger endohedral La@C 82 molecules suggested that the adsorption of an endohedral molecule is similar to that of a fullerene without the presence of an endohedral atom [13].…”
Section: Introductionmentioning
confidence: 99%